The celebrations and banquets of the Inca: The remains of camelids of Tambo Viejo - Valdez, Lidio M. (2022)
South American camelids played key roles within the Inca empire. In addition of providing primary products, such as meat and hide, they were important sources of wool, fuel, and fertilizer, while llamas were also valued as beasts of burden. Moreover, ethnohistorical accounts indicate that on occasion of the ritual celebrations organized by the state, young male camelids were regularly slaughtered in the hundreds. The reports further indicate that some of the sacrificed animals were burned, and their ashes thrown ceremoniously into a river, while others were distributed and consumed during the same public ceremonies. Recent archaeological research carried out at the Inca provincial center of Tambo Viejo of the Acari Valley resulted in the finding of an excellent collection of camelid bones; its analysis demonstrates that the bones and their respective epiphyses were about to fuse or had just fused, indicating that the camelids slaughtered at Tambo Viejo were physically fully developed animals.